From Measurement to Action: Initiating the Simultaneous Alleviation of Poverty and Food Insecurity Policy in Indonesia - Siectio Dicko Pratama; Rizvaldi Abdul Muid; K. Nurika Damayanti (Salus Cultura)
Indonesia is committed to achieving the Sustainable Development Goals (SDGs) by 2030, with a focus on eradicating poverty and hunger. However, current trends indicate a significant gap between the targets and the realities on the ground. This study addresses the intertwined issues of food insecurity and poverty, both of which present major obstacles to achieving the first and second SDG goals. Using the Alkire-Foster method to develop a multidimensional Food Insecurity Ratio, this research aims to trigger the simultaneous alleviation of food insecurity and poverty by utilizing the benefit of the food insecurity measure in Indonesia. Drawing on data from the 2022-2023 Socioeconomic Survey, the study highlights the persistent regional disparities in food insecurity, with Eastern Indonesia, particularly Papua and Maluku, facing the highest levels. The results indicate that while poverty rates have decreased, food insecurity persists, with 50% of food-insecure individuals also living in poverty. The findings underscore the need for integrated policies that address both issues simultaneously. By targeting specific regional challenges, such as access to food, nutrition, and vulnerability to shocks, this study offers policy recommendations to optimize resources and accelerate progress towards the SDGs.